Serum total testosterone and the prognosis of patients with advanced liver disease: a systemic review and meta-analysis - Zhang, Xiao-Yu; Xu, Heng-Han; Ma, Jian-Hui; Liu, Yang; Li, Han; Tan, Hao-Qian; Liu, Jun-Ying (PeerJ, 2026)
Background Advanced liver disease (ALD) is associated with significant morbidity and mortality worldwide. Emerging evidence suggests that sex hormonal imbalances, particularly low serum total testosterone (TT) levels, may influence the prognosis of patients with ALD. This meta-analysis aimed to evaluate the association between serum TT levels and the prognosis of patients with ALD. Methods Comprehensive searches of PubMed, Embase, and Web of Science were performed from the inception of the searched databases up to November 13, 2025, to identify observational studies assessing the association between serum TT levels and the risk of all-cause mortality or liver transplant (LT) among patients with ALD. Pooled risk ratios (RRs) with 95% confidence intervals (CIs) were calculated using a random-effects model to account for the potential influence of heterogeneity. This systematic review was registered in PROSPERO (CRD42024578870). Results Eight cohort studies encompassing 1,989 patients were included in the analysis. Findings demonstrated that low serum TT levels were significantly associated with an increased risk of all-cause mortality or LT during follow-up (RR: 1.87, 95% CI [1.57–2.23], p < 0.001; I2 = 0%). Sensitivity analyses, including those limited to male patients, confirmed the stability of these results. Subgroup analyses revealed consistent associations across various study designs, geographic regions, patient ages, TT cutoff values, follow-up durations, and quality assessments (p for subgroup difference, all > 0.05). Conclusion Lower serum TT levels are significantly associated with a higher risk of all-cause death or LT in patients with ALD, indicating their potential utility as prognostic biomarkers.
Keywords: Advanced liver disease; Androgen; Meta-analysis; Mortality; Testosterone